Síntese quimioenzimática da (R)-mexiletina, um fármaco antiarrítmico, e análogos - Carvalho, Ana Caroline Lustosa de Melo (2017)
(R)-Mexiletine, an antiarrhythmic drug, and the analogues were synthesized following chemoenzymatic routes. Rac-1-(2,6-dimethylphenoxy)propane-2-yl acetate (rac-4a) was used as the "template" substrate in the enzymatic kinetic resolution (EKR), using lipase, via hydrolysis reaction. After a screening, Candida antarctica B, CAL-B, immobilized on acrylic resin (Novozym 435®), Thermomyces lanuginosus immobilized on immobead-150 (TLL) and Amano lipase AK from Pseudomonas fluorescens were selected, which led to values of 50% conversion, enantiomeric excess values of alcohol and remaining acetate > 99% and enantioselectivity (E) > 200. At the same time, EKR was performed via acetylation of rac-1-(2,6-dimethylphenoxy)propan-2-ol (rac-3a) mediated by Novozym 435®, TLL and Amano lipase AK lipase from P. fluorescens in organic solvent. In the presence of TLL in both toluene and THF, the acetate and the remaining alcohol were obtained with enantiomeric excess > 90% and conversion values close to 50%. The most promising results were obtained in the EKR of rac-4a via the hydrolysis reaction, which was the reaction used to extend the EKR study to rac-4b-d [b: 1-(2,4-dimethylphenoxy)propane-2-yl acetate; c: 1-(o-tolyloxy)propane-2-yl acetate; d: 1-(naphthalen-1-yloxy)propane-2-yl acetate, modifying some parameters such as: temperature, solvent and reaction time. The remaining (S)-acetates have the desired configuration to be used as intermediates in the preparation of the (R)-Mexiletine analogues. For EKR of rac-4b, in 24 h, P. fluorescens Amano lipase AK was most efficient both in the presence of acetonitrile as co-solvent [(S)-acetate: 98% ee] and in the absence of co-solvent [(S)-acetate: > 99% ee]. For the substrate rac-4c, in 24 h, the best conditions to obtain (S)-4c included the use of TLL in the absence of co-solvents [(S)-acetate: > 99% ee]. For the substrate rac-4d, both TLL and Amano lipase AK from P. fluorescens, in the presence of acetonitrile as co-solvent, in 48 h, afforded (S)-acetate 4d in ee > 99%. All absolute configurations of the analogues were determined by Mosher’s method and proved that the EKRs followed the Kazlauskas’ rule. Thereafter, the (S)-acetates 4a-d were hydrolyzed, leading to corresponding (S)-alcohols 3a-d, in yields of 58 to 70%. The (S)-alcohols 3a-d were converted to the (R)-azides 5a-d in yields between 60 and 84%. Finally, (R)-azides 5a-d were transformed into (R)-amines, 6a [(R)-Mexiletine] and (R)-6b-d analogues in yields between 65 and 95%. Overall yields varied between 13 and 36%.